Medial Patellofemoral Ligament Repair Versus Reconstruction for Recurrent Patellar Instability: Two-Year Results of an Algorithm-Based Approach. Issue 3 (16th March 2017) - Dragoo, Jason L.; Nguyen, Michael; Gatewood, Corey T.; Taunton, Jacob D.; Young, Simon
Background: Patellar instability remains a challenging problem for both the patient and surgeon. Medial patellofemoral ligament (MPFL) repair has historically had poor results, and due to this, there is currently a trend toward reconstruction. Purpose/Hypothesis: This study was undertaken to investigate experience with repair versus reconstruction of the MPFL using a multifactorial treatment algorithm approach. Our hypothesis was that there will be no significant difference in outcome scores between patients in the MPFL repair and reconstruction groups. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 24 patients with recurrent (≥2) lateral patellar dislocations were included. All had failed nonoperative treatment for more than 6 months, and all were observed for a minimum of 2 years. First, magnetic resonance imaging (MRI) was used to find the location of the MPFL tear. A tilt test was used to determine whether a lateral retinacular lengthening was required to allow the patella to have neutral tilt. If the MRI showed a tibial tubercle–trochlear groove (TT-TG) distance greater than 20 mm, a tibial tubercle osteotomy (TTO) was recommended. An MPFL reconstruction was performed if the entire ligament was inadequately visualized on MRI or if it was torn from both insertion sites. Failure was defined as recurrent lateral patellar instability after surgery. As a secondary outcome measure, Knee injury and Osteoarthritis Outcome Score (KOOS), Lysholm score, and Tegner score were calculated. Results: All patients were evaluated with a mean follow-up of 51 months (range, 25-79 months). Sixteen patients initially underwent MPFL repair, 8 underwent reconstruction, and 3 also underwent TTO. MPFL reconstructions were performed in all patients who underwent TTO. One MPFL repair was to the anatomic femoral origin and 15 were to the patellar insertion corresponding to the site of tearing on MRI. A lateral retinacular lengthening was performed in 21 patients. There was 1 failure in the repair group (6%) and none in the reconstruction group. However, the patient who failed had a TT-TG distance of 26 mm but refused a TTO. She subsequently underwent revision with a TTO and MPFL reconstruction and did not have any further instability events. There were no significant differences between groups for any of the secondary outcome scores. Conclusion: Using an algorithm-based approach, MPFL repair or reconstruction may lead to clinically acceptable results at 2-year follow-up.